Penafsiran ayat-ayat amanah dalam al-Qur'an - Irfan, Irfan (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2019)
Every human being born into this world has a mandate (amanah) and responsibility, be it a trust that is related to Allah SWT, fellow human beings, or to yourself. But the reality is that there are still people who do not yet know the importance of that mandate so that there are people who use their position as a tool to get what they want without caring about the people around them. From ignorance and human ignorance itself so that many people who work are not in accordance with their fields of expertise. Even though in the Koran it was mentioned how important it is to maintain a mandate. Therefore, the writer will elaborate on the interpretation of the verses about the mandate in the Qur'an. With this study, it is expected to be able to provide a more easily understood understanding of the interpretation of the verses of the mandate contained in the Qur'an, so that it can quickly practice and practice it in daily life.